Reflections of Enculturation and Acculturation in Chabacano Folklores of Zamboanga City - Ebrole, Rodney I; Reyes, Aubrey F (International Journal of Membrane Science and Technology, 2023)
This qualitative, descriptive, and analytical research study aimed to describe the perception of Zamboangueño-Chabacano through a sociological lens. The examination of the data centers on Chabacano folklore gathered from several trustworthy sources. The enculturation and acculturation types of culture were used to categorize these non-material cultures. It is essential to comprehend Zamboangueo-Chabacano culture to preserve cultural traditions and develop programs that may be used in the classroom to promote greater literacy. Seventeen of the thirty-five described civilizations are enculturated, while 18 are acculturated. The Chabacano folklores that best capture the Zamboangueo-Chabacano culture emphasize respect for other people’s languages, races, and cities, a firm belief in God, perseverance, diligence, courage, resourcefulness, and an acceptance of paranormal phenomena (kababalaghan). The research’s findings corroborate the idea that the influence of Spanish culture and great devotion to Catholicism played an essential role in the lives of the Zamboangueño-Chabacano by showing that the majority of the culture depicted in Chabacano folklore is acculturation.